Study on the role of \(TDRD1\) variants in male infertility among 310 Vietnamese individuals - Duc Duy, La; Minh Nguyet, Nguyen; Thi Thu Hue, Huynh; Thuy Duong, Nguyen (Academia Journal of Biology, 2023)
Infertility is a global reproductive health burden affected by various genetic factors, including spermatogenic defects. The instability of the germ cells’ genome caused by the unregulated replication of transposable elements is one of the causes of spermatogenic impairment. Tudor domain-containing 1 (TDRD1) expressed only in germ cells plays a significant role in the piRNA (PIWI-interacting RNA) pathway to maintain genome integrity via suppressing transposon elements during spermatogenesis. Despite the protein’s role in male germline development, TDRD1 has not been studied intensively. In this study, we established the relationship between male infertility and single nucleotide polymorphisms (SNPs) of TDRD1 (rs541192490, rs77559927) among 310 Vietnamese men (160 infertile patients and 150 healthy controls). Genotypes of single nucleotide polymorphisms of the TDRD1 gene (SNPs) were identified using the PCR-RFLP method. The results showed that TDRD1 SNPs were not associated with male infertility in all three test models (additive, dominant, and recessive) (p-value > 0.05). Haplotype analysis of the two SNPs also showed similar findings. This study would contribute to the knowledge of TDRD1’s association with male infertility in the Vietnamese population.